The Effects of Nebivolol on Moderate Traumatic Brain Injury in a Rat Model: Implications for Pediatric Neuroprotection - Ali Akbar Esfahani, Mohammad; Faghih , Hossein; Talebi, Samira; Eslamian, Mohammad; Rasouli , Hamid Reza; Ahmadpour, Fathollah (Iranian Journal of Child Neurology, 2026)
Objectives: Traumatic Brain Injury (TBI) is a significant public health problem. Nuclear factor E2-related factor 2 (Nrf2) is a transcription factor regulating oxidative stress and inflammation after TBI. This study examined the neuroprotective potential of Nebivolol in a rat model of moderate TBI, with a focus on implications for pediatric therapy. Materials & Methods: Twenty-one male Wistar rats (230 ± 10 g) were included. The animals were trained using the Morris Water Maze (MWM) test, and mTBI was induced using a pendulum-based method. Nebivolol was administered at a dose of 0.05 mg/kg daily from day 8 to day 21 post-injury. Behavioral assessments were performed using the MWM, while structural brain changes were evaluated via micro-computed tomography (micro-CT). Inflammatory biomarkers were also analyzed. Results: The results revealed significant post-TBI increases in inflammatory markers (CRP, cortisol) and decreases in prolactin levels in control animals (p<0.01). Nebivolol treatment attenuated these biochemical changes while maintaining cardiovascular stability. The MWM demonstrated improved late-phase cognitive recovery in Nebivolol-treated subjects despite initial learning impairment. Nebivolol treatment significantly attenuated these biochemical changes. While early learning in the MWM was impaired, animals treated with Nebivolol established superior late-phase cognitive recovery. It suggests enhanced neuroplasticity. Nebivolol also maintained cardiovascular stability without inducing bradycardia. Conclusion: The results demonstrated that Nebivolol treatment significantly modulates TBI-induced physiological changes, such as CRP and cortisol, while maintaining cardiovascular stability. Although it showed protective effects against TBI-related stress responses, the observed neuroendocrine alterations suggest complex systemic interactions. Nebivolol reduces inflammation, stabilizes cardiovascular function, and finally promotes cognitive rehab. The pleiotropic profile of Nebivolol promises reliable research in pediatric-focused models and forthcoming clinical trials.